Analysis of clinical features, prognosis and comprehensive therapeutic strategies in 261 patients with limited-stage esophageal small cell carcinoma - LIU Di, NI Jianjiao, ZHAO Kuaile, XIANG Jiaqing, ZHANG Zhen, ZHANG Junhua (Zhongguo aizheng zazhi)
Background and purpose: Limited-stage (LS)-small cell esophageal carcinoma (SCEC), characterized by high aggressiveness and an extremely poor prognosis, lacks standardized staging systems due to its rarity. Consequently, no randomized controlled clinical trials exist to guide therapeutic strategies, necessitating reliance on extrapolated protocols from small cell lung cancer (SCLC) paradigms, though clinical outcomes remain dismal. This study aimed to analyse survival outcomes, prognostic factors, failure patterns and therapeutic strategies in patients with LS-SCEC. Methods: We conducted a retrospective single-center study of LS-SCEC patients diagnosed and treated at Fudan University Shanghai Cancer Center from January 2006 to June 2023. Clinicopathological data for diagnosis, staging and follow-up were rigorously collected. Patients with mixed esophageal tumors in whom small cell carcinoma was not the predominant histological component (<50%) were excluded. Continuous variables were presented as $\bar{x} ± s$. Categorical variables were summarized as counts and percentages, with intergroup comparisons performed using χ2 test or Fisher’s exact tests. Survival analysis was performed using the Kaplan-Meier method, and Cox regression was used to analyse factors related to prognosis. A two-sided P<0.050 was considered statistically significant. A 1∶1 nearest-neighbour propensity score matching was applied to compare survival outcomes between patients undergoing radical chemoradiotherapy and those receiving radical surgery followed by adjuvant chemotherapy. Results: Of 261 eligible LS-SCEC patients included, the median follow-up duration was 72.7 months (95% CI: 52.0-92.4), with a median cancer-specific survival (CSS) of 24.5 months (95% CI: 19.7-29.3) and a 5-year CSS rate of 32.8%. The median progression-free survival (PFS) was 12.0 months (95% CI: 10.7-13.3). Among these, 67 patients remained recurrence-free, and 169 patients exhibited disease progression after first-line treatment. Distant metastasis was the predominant recurrence pattern (131 patients, 77.5%), whereas locoregional recurrence occurred in only 38 patients (22.5%). The most frequent metastatic sites were liver (54 patients), followed by bone (25 patients), brain (24 patients), and lung (23 patients). The number of chemotherapy cycle and TNM stage (8th edition) were independent prognostic factors for CSS and PFS in LS-SCEC patients. Comparative analysis of radical surgery with adjuvant chemotherapy versus radical chemoradiotherapy revealed no statistically significant differences in CSS and PFS (P>0.05), even after propensity score matching. Patients with cervical/upper thoracic tumors, longer tumor lengths, and advanced stages were more likely to receive chemoradiotherapy; additionally, the chemoradiotherapy group had a higher proportion of patients completing ≥4 chemotherapy cycle. Conclusion: This large-sample retrospective study with comprehensive datasets and long-term follow-up demonstrated comparable survival outcomes between radical chemoradiotherapy and radical surgery plus adjuvant chemotherapy for LS-SCEC. A minimum of 4 chemotherapy cycle was associated with improved prognosis. SCEC is associated with a high risk of distant metastasis and marked heterogeneity. Therefore, the treatment of LS-SCEC should prioritize an individualized approach.